Analisis Regresi Logistik Biner dalam Penentuan Faktor-Faktor yang Mempengaruhi Ketepatan Waktu Lulus Mahasiswa UIN Alauddin Makassar - Sri Dewi Anugrawati; Nurhikma; Iyut Wahyu Saputri; Khalilah Nurfadilah (Program Studi Matematika Universitas Sulawesi Barat, 2023)
This research is an application/applied research, namely by taking or collecting data and analyzing it using a binary logistic regression model to determine the factors that influence the accuracy of graduating students at UIN Alauddin Makassar. The type of data used in this research is secondary data. These data originally from undergraduate students data 0f 8 faculties obtained from the PUSTIPAD Information System of UIN Alauddin Makassar Rector Class of 2016. Undergraduate/D-IV program students are declared to graduate on time if they complete their studies at tertiary institutions for less than or equal to 8 semesters or you could say 4 years, with a minimum number of credits of 144 credits. To determine the binary logistic regression model, parameter significance tests were carried out simultaneously using the G test and partially using the Wald test. Then test the fit of the model by measuring the chi-square value and the Hosmer and Lowshow test at a significant level of 5%. The results showed that there were three factors that influenced the timeliness of graduation accuracy, namely gender (X1), IPK (X3) and educational background (X4)